Research of structures with corrugated photoreceiving surface - Karimov, A.V.; Yodgorova, D.M.; Yakubov, E.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Goffered photoreceiver surface in active regions perspective for manufacturing photosensitive structures can be form by chemical and epitaxial technology. Microreliefs are created on initial surface of semiconductor material by chemical method that comprises etching in special solutions. Epitaxial technology allow to obtain goffered layers on etched surface and on the smooth one as well using growth from a liquid phase. In the case of smooth surfaces, chosen are parameters of solutionmelt providing the growth of the layer. The structures with the formed goffered surface have high photosensitivity and a wide optical range for their operation.